MAYBELLINE PURCHASE INTENTION: THE INTERPLAY OF INFLUENCER MARKETING, BRAND IMAGE, AND ELECTRONIC WORD OF MOUTH - Blegur, Petrisia; Cokki , Cokki (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to analyze the influence of influencer marketing and brand image on the purchase intention of Maybelline products in Jakarta, with electronic word of mouth as a mediating variable. The research sample consisted of 150 respondents who were selected using convenience sampling. Data was collected using a questionnaire and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique. The results of the study indicate that influencer marketing have a direct influence on purchase intention, but not an indirect one through electronic word of mouth. On the other hand, brand image has a direct positive influence on purchase intention, as well as an indirect influence through electronic word of mouth.